Ecclesiastics as the Physiology of the Reformed Church in the Perception of László Ravasz - Árpád KULCSÁR (Studia Universitatis Babeş-Bolyai. Theologia Reformata Transylvanica)
László Ravasz (1882–1975), former professor of practical theology (1907–1921) at the Transylvanian Reformed Faculty, Cluj, as a young professor introduced a new subject in the preparation and education of prospective Reformed pastors. Ecclesiastics appears in his works in the early 20th century and persists over the decades in the scientific discussions of Reformed theologists. In this paper, I examine László Ravasz’s perception of ecclesiastics and Reformed practical theology. In its early years, the subject struggles with the lack of proper terminology and needs to clarify several issues. László Ravasz proves and justifies that practical theology needs ecclesiastics as a prolegomenon. The most important questions, such as how? what? why? who? where?, can only be answered through a theoretical clarification by ecclesiastics. With the help of mostly Dutch practical theological literature, I also examine how relevant László Ravasz’s thoughts are nowadays, and my conclusion is that by pioneering the issue of ecclesiastics László Ravasz formed generations of pastors in their profession.